Kecemasan pada Dewasa Awal Akibat Fear of Missing Out (FoMO) - Nadia Khairina; Dyah Septi Ruli Rahmawati; Friska Indriani (Flourishing Journal, 2024)
New challenges due to major changes in early adulthood such as changing environments, academic demands, and pressures in building personal identity are the main triggers for intense feelings of fear of missing out (FoMO). FoMO creates anxiety about being left behind from important experiences in social life, triggering feelings of anxiety and lack of life satisfaction because individuals feel marginalized from valuable moments that are considered important by their social environment. The urge to engage in various activities and expand social networks becomes a source of pressure if unable to participate in these moments. This study aims to identify and understand FoMO in relation to anxiety in early adulthood and the factors that influence it. This study uses a descriptive qualitative approach with a structured interview method on two early adult subjects who have experienced FoMO. The results of this study indicate that dependence on social media among 19-25 year olds gives rise to fear of missing out (FoMO), which creates feelings of anxiety, self-comparison, and fear of missing out on information, with the impact of feelings of loneliness and psychological stress. AbstrakTantangan baru karena perubahan besar pada dewasa awal seperti pergantian lingkungan, tuntutan akademis, dan tekanan dalam membangun identitas pribadi menjadi pemicu utama perasaan fear of missing out (FoMO) yang intens. FoMO menciptakan kecemasan akan tertinggal dari pengalaman-pengalaman penting dalam kehidupan sosial, memicu perasaan cemas dan kurangnya kepuasan hidup karena individu merasa terpinggirkan dari momen-momen berharga yang dianggap penting oleh lingkungan sosial mereka. Dorongan untuk terlibat dalam berbagai kegiatan dan memperluas jejaring sosial menjadi sumber tekanan jika tidak mampu ikut serta dalam momen-momen tersebut. Penelitian ini bertujuan untuk mengidentifikasi dan memahami FoMO kaitannya dengan kecemasan pada dewasa awal dan faktor-faktor yang mempengaruhinya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode wawancara terstruktur pada dua subjek dewasa awal yang pernah mengalami FoMO. Hasil penelitian ini menunjukkan bahwa ketergantungan pada media sosial di kalangan usia 19-25 tahun memunculkan fear of missing out (FoMO), yang menciptakan rasa cemas, perbandingan diri, dan ketakutan ketinggalan informasi, dengan dampak berupa perasaan kesepian dan tekanan psikologis.